Look, but to the left: A rare case of gallbladder sinistroposition and comprehensive literature review. (November 2021) - Almas, Talal; Murad, Muhammad Faisal; Mansour, Eyad; Khan, Muhammad Kashif; Ullah, Muneeb; Nadeem, Faisal; Shafi, Adil; Khedro, Tarek; Almuhaileej, Mohammad; Abdulhadi, Abdulaziz; Alshamlan, Abdulaziz; Nagarajan, Vikneswaran Raj; et al.
Abstract: Left-sided gallbladder (LSGB) is a rare anatomic variation that, while benign in the context of its transposition, is of significant intraoperative importance. Due to its association with other anatomic anomalies involving key structures in the hepatobiliary system, discovering it intraoperatively as opposed to preoperatively suddenly increases the difficulty of a gallbladder procedure. Highlights: 1) Left-sided gallbladder (LSGB) is a rare anatomic variation that, while benign in the context of its transposition, is of significant intraoperative importance. 2) Although laparoscopic cholecystectomy of a LSGB is safe, it is associated with higher risk of complications such as common bile duct injury. 3) Most cases of a LSGB are diagnosed intraoperatively, and this sudden discovery during the procedure can increase the difficulty, duration, and stress of the procedure due to the other potential anatomic anomalies that LSGB is associated with in the hepatobiliary system.